2015
DOI: 10.1093/treephys/tpv068
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization with urea, ammonium and nitrate produce different effects on growth, hydraulic traits and drought tolerance inPinus taedaseedlings

Abstract: Urea fertilization decreases Pinus taeda L. growth in clay soils of subtropical areas. The negative effect of urea is related to changes in some hydraulic traits, similar to those observed in plants growing under drought. The aims of this work were (i) to determine whether different sources of nitrogen applied as fertilizers produce similar changes in growth and hydraulic traits to those observed by urea fertilization and (ii) to analyze the impact of those changes in plant drought tolerance. Plants fertilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…Analysis of the levels of gene expression indicate that ammonia and nitrate modulate the expression of NAC TFs more than urea. A study utilizing Pinus taeda revealed that fertilization with ammonium, nitrate, or urea produces different effects on growth and drought tolerance [99]. Results of the current analysis indicate that AtNAC8 and AtNAC91 are the major NAC TFs involved in nitrogen assimilation during plant growth.…”
Section: Nac Tfs Are Expressed In a Spatiotemporal Mannermentioning
confidence: 75%
“…Analysis of the levels of gene expression indicate that ammonia and nitrate modulate the expression of NAC TFs more than urea. A study utilizing Pinus taeda revealed that fertilization with ammonium, nitrate, or urea produces different effects on growth and drought tolerance [99]. Results of the current analysis indicate that AtNAC8 and AtNAC91 are the major NAC TFs involved in nitrogen assimilation during plant growth.…”
Section: Nac Tfs Are Expressed In a Spatiotemporal Mannermentioning
confidence: 75%
“…Analysis of the levels of gene expression indicate that ammonia and nitrate modulate the expression of NAC TFs more than urea. A study utilizing Pinus taeda revealed that fertilization with ammonium, nitrate, or urea produces different effects on growth and drought tolerance 57 . Results of the current analysis indicate that AtNAC8 and AtNAC91 are the major NAC TFs involved in nitrogen assimilation during plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in dry soil, the diffusion of nitrate and ammonium in the soil is slower than the diffusion in soil at field capacity ( Gregory , ). In this context, N fertilization increases the concentration of inorganic forms of N in the soil solution ( Faustino et al, ), acidifies the soil solution and cell wall ,and consequently facilitates the replenishment of N to the depletion zone in the rhizosphere and stimulates root growth ( Bloom et al, ). This indicates that N fertilization plays a pivotal role in alleviating the negative effects of water stress on plant growth and development.…”
Section: Discussionmentioning
confidence: 99%